Impacts of dietary animal and plant protein on weight and glycemic control in health, obesity and type 2 diabetes: friend or foe? - Anjom-Shoae, Javad; Feinle-Bisset, Christine; Horowitz, Michael (Frontiers in Endocrinology, 2024)
It is well established that high-protein diets (i.e. 25–30% of energy intake from protein) provide benefits for achieving weight loss, and subsequent weight maintenance, in individuals with obesity, and improve glycemic control in type 2 diabetes (T2D). These effects may be attributable to the superior satiating property of protein, at least in part, through stimulation of both gastrointestinal (GI) mechanisms by protein, involving GI hormone release and slowing of gastric emptying, as well as post-absorptive mechanisms facilitated by circulating amino acids. In contrast, there is evidence that the beneficial effects of greater protein intake on body weight and glycemia may only be sustained for 6–12 months. While both suboptimal dietary compliance and metabolic adaptation, as well as substantial limitations in the design of longer-term studies are all likely to contribute to this contradiction, the source of dietary protein (i.e. animal vs. plant) has received inappropriately little attention. This issue has been highlighted by outcomes of recent epidemiological studies indicating that long-term consumption of animal-based protein may have adverse effects in relation to the development of obesity and T2D, while plant-based protein showed either protective or neutral effects. This review examines information relating to the effects of dietary protein on appetite, energy intake and postprandial glycemia, and the relevant GI functions, as reported in acute, intermediate- and long-term studies in humans. We also evaluate knowledge relating to the relevance of the dietary protein source, specifically animal or plant, to the prevention, and management, of obesity and T2D.